Analisis Perbedaan Kinerja Keuangan Pemerintah Daerah Kabupaten Gorontalo antara Sebelum dan Saat Pandemi COVID-19 Periode 2017-2022 - Muhammad Farhan Ali; Nilawaty Yusuf; Victorson Taruh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aimed to test the differences in the financial performance of the Gorontalo Regency local government before and during the COVID-19 pandemic. This research employed a quantitative method. The population in this study was the Financial Statements of the Gorontalo Regency Government for the period 2017-2022. The sampling used was purposive sampling, where sample members were selected deliberately according to the research objectives and specific criteria. The data source used was secondary data, specifically budget realization reports. The sample consisted of 24 quarterly reports in the form of LRA for the period 2017-2022. The data collection technique used was documentation. Additionally, the data analysis methods employed was inferential statistical analysis. The results of the study show no difference in the financial performance of the Gorontalo Regency local government before and during the COVID-19 pandemic in terms of independence ratio, PAD (Local Own-Source Revenue) effectiveness, efficiency, operational expenditure, and capital expenditure ratios.